Characterization of a broadly expressed human leucocyte surface antigen MEM-43 anchored in membrane through phosphatidylinositol - Stefanová, I; Hilgert, I; Kristofová, H; Brown, R; Low, M G; Horejsí, V (Molecular immunology, 1989)
A monoclonal antibody MEM-43 was prepared, which recognizes an antigen expressed on all peripheral blood leucocytes, on erythrocytes and several cell lines, but is absent from U937, Nalm-6, Daudi and Raji cell lines. The antigen isolated by immunoaffinity chromatography from several cell lines is an 18,000-25,000 mol. wt glycoprotein. An apparently identical antigen isolated from erythrocytes binds to several lectins and has a 14,000 mol. wt polypeptide backbone, modified by an endoglycosidase F-sensitive carbohydrate moiety. The epitope recognized is reduction-sensitive. The sequence of N-terminal 17 amino acid residues was determined; five out of six N-terminal amino acids are identical to those found at the N-terminus of the mouse lymphocyte surface antigen Ly-6C. The antigen is completely released from the cell surface after treatment with phosphatidylinositol-specific phospholipase C.
Keywords: Electrophoresis, Polyacrylamide Gel; sekvence aminokyselin; buněčné linie; lidé; Cell Membrane; Antigens, Surface; Cell Line; Phosphatidylinositols; fosfatidylinositoly; myši; Humans; Antibodies, Monoclonal; Mice; monoklonální protilátky; zvířata; buněčná membrána; Glycoproteins; elektroforéza v polyakrylamidovém gelu; Animals; molekulární sekvence - údaje; Leukocytes; Molecular Sequence Data; leukocyty; antigeny povrchové; glykoproteiny; Amino Acid Sequence